Geographic Mosaics of Fly Pollinators With Divergent Color Preferences Drive Landscape-Scale Structuring of Flower Color in Daisy Communities - Ellis, Allan G.; Anderson, Bruce; Kemp, Jurene E. (Frontiers in Plant Science, 2021)
The striking variation in flower colour across and within Angiosperm species is often attributed to divergent selection resulting from geographic mosaics of pollinators with different colour preferences. Despite the importance of pollinator mosaics in driving floral divergence, the distributions of pollinators and their colour preferences are seldom quantified. The extensive mass-flowering displays of annual daisy species in Namaqualand, South Africa, are characterised by striking colour convergence within communities, but also colour turnover within species and genera across large geographic scales. We aimed to determine whether shifts between orange and white-flowered daisy communities are driven by the innate colour preferences of different pollinators or by soil colour, which can potentially affect the detectability of different coloured flowers. Different bee-fly pollinators dominated in both community types so that largely non-overlapping pollinator distributions were strongly associated with different flower colours. Visual modelling demonstrated that orange and white flowered species are distinguishable in fly vision, and choice experiments demonstrated strongly divergent colour preferences. We found that the dominant pollinator in orange communities has a strong spontaneous preference for orange flowers, which was not altered by conditioning. Similarly, the dominant pollinator in white communities exhibited an innate preference for white flowers. Although detectability of white flowers varied across soil types, background contrast did not alter colour preferences. These findings demonstrate that landscape-level flower colour turnover across Namaqua daisy communities is likely shaped by a strong qualitative geographic mosaic of bee-fly pollinators with divergent colour preferences. This is an unexpected result given the classically generalist pollination phenotype of daisies. However, because of the dominance of single fly pollinator species within communities, and the virtual absence of bees as pollinators, we suggest that Namaqua daisies function as pollination specialists despite their generalist phenotypes, thus facilitating differentiation of flower colour by pollinator shifts across the fly pollinator mosaic.